Analisis Transitivitas pada Penokohan dalam Cerpen Bas les masques dan Délivrance: Kajian Linguistik Sistemik Fungsional - Prasetyo, Gilang Tegar; Sajarwa, Sajarwa (Sasdaya: Gadjah Mada Journal of Humanities, 2024)
This study aims to describe the characterizations in the “Bas les masques” and “Délivrance” short stories based on the transitivity process and describe the characterization techniques used in the “Bas les masques” and “Délivrance” short stories. This research uses a descriptive approach with a qualitative method. The data are the clauses explaining characterizations in the short stories “Bas les masques” by Benoît Broyart and “Délivrance” by Jean-Paul Nozière. The data collection of this research is carried out by scrutinizing and note-taking techniques. The data are analyzed using the transitivity theory in Halliday’s Systemic Functional Linguistics and Nurgiyantoro’s character depiction theory. The results of this study indicate that the characterization in these two stories are dominantly described by material process, i.e. 8 clauses (35%) in the “Bas les masques” short story and 9 clauses (39%) in the “Délivrance” short story. The processes that are not found are behavioral process because the characters’ behavior cannot be explained from their own perspective. Regarding the character depiction techniques, the two short stories both use conversation techniques and other character’s reaction techniques. Apart from that, there is also the stream of consciousness technique which is only used in “Bas les masques” short story and the character reaction technique which is only used in “Délivrance” short story. From the results of this research, it can be concluded that transitivity analysis can support the study of characterization in literary works because the character's personality can be represented through their experiences in the story.